Editorial: Biodegradable Matrices and Composites - Pegoretti, Alessandro; Dong, Roger; Slouf, Miroslav (Frontiers Media, 2020)
Biodegradable and ecofriendly materials attract an increasingly high attention from polymer and composite researchers and manufactures as they can contribute to a more sustainable global development policy, to significantly reduce non-recyclable plastic wastes and limit the impact on the environment. A thorough understanding of both advantages and limitations of biodegradable matrices and composite materials is the key to their reasonable, precisely targeted and effective applications in order to benefit wide communities. The attention in the field of real applications is focused mostly on packaging materials, but automotive, construction and agriculture are also important fields. As for medical applications, biodegradable matrices and composites are used mostly due to their tunable biodegradability, which is often combined with controlled and localized drug release. The term of biodegradable composites comprises a wide range of at least two-phase hybrid materials in which either fillers or matrix or both must be chosen from biodegradable sources. Hence, those matrices based on biodegradable polymers are also well recognized as biodegradable matrices. On the other hand, fillers being the minority phase act as a reinforcement in most biodegradable composites. However, with respect to polymer blends, the minority phase often plays a different role as an impact modifier, a plasticizer or a compatibilizer, as opposed to its drug carrier status in medical applications. Particular cautions should always be taken in the case of composites containing synthetic polymers as matrices, whose biodegradability, biocompatibility and/or environmental impact may be rather questionable. On the other hand, composites containing bio-based biodegradable polymers as matrices can be fine-tuned to exhibit good tensile, impact and creep properties in spite of lower resistance to moisture, leading to poor mechanical performance at high humidity or aqueous conditions. The research topic on Biodegradable Matrices and Composites is focused on recent advances in preparation and characterization of biodegradable polymeric matrices and their composites with the main objective to understand their processing-structure-property relationship at nano-, micro- and macroscale. Both conventional biodegradable polymers and related biodegradable composites and more recent biodegradable nanocomposites reinforced with nanoparticles and nanofillers are covered to address various aspects, including but not limited to their mechanical, thermal and barrier properties, biodegradability, environmental sustainability, renewability and recyclability, limitations and applications in building constructions, automobiles, medical devices and material packaging.